2018
DOI: 10.1002/hpm.2646
|View full text |Cite
|
Sign up to set email alerts
|

Use of Lean techniques in health care in Spain to improve involvement and satisfaction of workers

Abstract: The purpose of this study was to improve the organization of work, reduce physical effort, and obtain greater satisfaction of workers in the Pre-analytical Area of the Clinical Biochemistry Service at the Miguel Servet University Hospital of Zaragoza, in Spain, by applying Lean techniques. Such techniques were applied in two steps to obtain a final situation where the reduction of the space occupied, the required physical effort, and the work time is clear. The satisfaction of the workers was analyzed during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Studies have shown that the use of other tools in conjunction with VSM has made it possible to expand the benefits of mapping [58]. It was observed that the 5S tool was cited in 18.2% of the articles that also used the VSM and results such as increased time for patient care, restructuring of the physical structure, visual management, reduction of lead time and improvement financial performance were also achieved [21,22,41,56,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the use of other tools in conjunction with VSM has made it possible to expand the benefits of mapping [58]. It was observed that the 5S tool was cited in 18.2% of the articles that also used the VSM and results such as increased time for patient care, restructuring of the physical structure, visual management, reduction of lead time and improvement financial performance were also achieved [21,22,41,56,59].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies [39,47,59] are noteworthy as they present a reduction in the distance traveled by professionals as a result of their interventions. These three used the VSM tool and two of them combined them with the spaghetti diagram; from this, we can infer that the combination of these two tools contributes to a better use of the physical space of the health units.…”
Section: Discussionmentioning
confidence: 99%
“…, 2017). In fact, bed management requires the development of a positive cultural environment to reach the commitment of workers (Sahoo, 2020; Damián Sanz et al. , 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…, 2016). The combined use of LSPs and LTPs reduces different types of waste in organizations (Damián Sanz et al. , 2019), solves problems in operations (Chiarini, 2013) and works cooperatively to obtain global results (Helmold, 2020).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite offering detailed descriptions through case studies, none of the papers in Table II provided clear guidelines that could be followed by hospital managers in the implementation process of lean healthcare. Damián Sanz et al (2019) and Gupta et al (2018) followed the logic of VSM, which is a helpful tool but not enough to constitute a complete implementation roadmap. Even though Ben-Tovim et al (2008) present a kind of roadmap, the authors only described three broad phases of the lean implementation process, without detailing enough to be useful for hospital managers.…”
Section: Lean Healthcare Implementationmentioning
confidence: 99%